Restorative Materials Exposed to Acid Challenge: Systematic Review and Meta-Analysis - Saeed Ateeq Kh. Al Zahrani; Yousef Saleh Alanazi; Mshari Suliman Al Mutairi; Nasser Tayeb Marir; Mohammed Saeed Alasiri; Nasser Mohammed Almutairi; Saeed Ali Alqahtani; Abdullah Alrafee; Turki Abdullah Alqarni; Bashayer Alosaimi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Hard tissue that is found in the teeth may be destroyed by erosion if acidic solutions are exposed to them for an extended period. The intake of non-alcoholic beverages, for instance soft drinks, is therefore the key factor that contributes to the development of tooth erosion in young people. Aim: To evaluate restorative materials exposed to acid challenge. Materials and methods: Following the criteria outlined in the Cochrane Handbook for systematic reviews of interventions and the PRISMA statement, this systematic review was conducted. The database searches were done in the following: the Cochrane Library, Web of Science, and MEDLINE (PubMed). Furthermore, the literature search employed the following search terms and their combinations: "fruit juice" OR "chemical degradation") AND ("Computer-Aided Design / Computer-Aided Manufacturing material" OR " ceramic " OR " porcelain " OR " ceramic/polymer material " OR " resin-ceramic "). Criteria for eligibility include in vitro and in vivo trails, investigations that investigate indirect restorative materials, as well as trails that assess the impact of erosion on the surface roughness or surface microhardness of restorative materials. Main findings and conclusion: A total of 1097 articles were found by electronic databases. Finally, five RCTs were selected. Our pooled meta-analysis for SR showed that, MD and 95% CI: 0.01[0.00, 0.02]. Weighted by fixed effect I2 and chi-p= 46% and <0.1. A mean change under 0 shows that the SR (surface roughness) is larger in the erosion group. Our pooled meta-analysis shows that the SMH (surface micro-hardness) is lesser in the erosion group with MD and 95% CI: 24.6[43.2, 6.01]. Weighted by random effects I2 and chi-p= 96% and <0.00001.